RECONSTRUCTION OF LEGAL FINDINGS AND REASONING ON ACEH'S LEGISLATIVE AUTHORITY WITHIN THE FRAME WORK OF SPECIAL AUTONOMY - Abdul Rahman Maulana Siregar; Musannif (CV. RADJA PUBLIKA, 2025)
This study aims to analyze the process of legal discovery and reasoning by the Aceh People's Representative Council (DPRA) in drafting qanuns, the extent to which these qanuns are in accordance with national laws and general legal principles, and the legal and social obstacles that arise in their implementation. The study uses a qualitative, normative-empirical method, with a literature study approach, semi-structured interviews with DPRA members, legal academics, and community leaders, and observations of the implementation of qanuns in the field. The results show that the Aceh DPRA applies legal reasoning to interpret national legal norms and adapt them to the local Acehnese context, and uses legal discovery to fill gaps or overlapping regulations. Although most qanuns are in line with the Aceh Special Autonomy Law and general legal principles, there are several qanuns that create potential legal conflicts with national regulations. Obstacles to qanun implementation include inconsistencies in norms, limited apparatus capacity, the complexity of qanuns for the community, and the lack of effective oversight mechanisms. The strategy of reconstructing legal discovery and reasoning through the integration of normative studies, empirical evaluation, and multi-stakeholder participation has been proven to be able to improve the quality of Aceh's legislation, ensuring that qanuns are more relevant, effective, and have legal and social legitimacy.